An Expert System for Diagnosing Monkeypox Diseases Using Forward Chaining Method by Mobile - Zul Indra,; Ramalia Noratama Putri,; Meilani Putri Efendy, (JIM - Journal International Multidisciplinary, 2023)
Abstract- Monkey pox is a disease transmitted by an animal virus. The virus is spread through direct contact with animals or from people who have been exposed to the disease. The development of technology in this era is quite rapid and is widely used as a means to improve human performance. The development of technology is currently widely used in the field of artificial intelligence. An expert system is a reasoning system that uses special knowledge to detect diseases. Today's society diagnoses itself a lot without knowing whether or not the disease is true. So this application helps to solve these problems. One of the diseases that uses artificial intelligence technology with the help of expert systems is monkey pox. In this application, the author uses the forward chaining method to form reasoning in the expert system. This method begins with collecting facts to make provisions as predicted. This application is intended to help people overcome confusion due to monkey pox while providing information to the general public about various types of diseases that exist in the community. This expert system is based on the study of literature such as texts, books, and journals. Well, from this application, users can choose the symptoms of the disease experienced by the patient, and the data will be processed to produce a diagnosis of the disease.